Students’ Perception of Using Telegram in Learning English at SMK Negeri 1 Bandar Masilam - br Depari, Marisa Yunita; Devi, Liza Sri; Sianipar, Ester; Herman, Herman (Universitas Nahdatul Ulama Surabaya, 2022)
This study is related to qualitative and uses a questionnaire method used by teachers and students when learning English in the classroom. The formulation of the problem is: Types of learning English by using telegram media which is used in the process of learning English for class X TKJ 1 SMK Negeri 1 Bandar Masilam students. This research uses qualitative research. The purpose of this study was to find out how the students of SMK Negeri 1 Bandar Masilam felt about using Telegram to learn English and how easy it was to use it. Telegram is one of the learning media. Telegram is a well-known tool in the education sector, especially at the college level. Telegram is used by some teachers as a learning medium. Telegram in language learning is being studied using qualitative research methods and questionnaire instruments. Twenty students from SMK Negeri 1 Bandar Masilam Class X Tkj-1 will take part in the lesson. Research and discussion showed that students' perceptions of the use of Telegram had a positive response. Most students agree that Telegam is easy to use and helps students learn English by allowing them to save and retrieve assignments and, in the case of Telegram, submit assignments. As a result, using Telegram to learn English is a wise decision